A novel control grid bias power supply for high-frequency pulsed electron beam welding. (November 2016) - Qi, Bojin; Fan, Jikang; Zhang, Wei; Liu, Fangjun; Wang, Haitao
Abstract: Pulsed electron beam welding (EBW) is a novel welding process of which the welding beam current is modulated to pulsed square wave. Pulsed EBW is considered a promising method to increase the depth-width ratio and improve the mechanical property of welding joints. Pulsed beam current can be achieved by regulating the bias voltage on the control grid electrode of electron gun. For further studying the characteristics of high frequency pulsed EBW, a novel control grid bias power supply is developed with advanced inverter control technology. This power supply includes one base circuit and one pulse circuit in series. The base circuit can generate DC voltage, and the pulse circuit can generate pulsed voltage. The frequency and duty ratio of pulsed voltage can be adjusted by the designed control circuit. Carrier wave technique is used to transmit the control signal and homemade insulating transformer is used to protect the control circuit from high voltage. EBW machines equipped with the developed power supply can realize both continuous EBW and 0–20 kHz pulsed EBW. The base value, peak value and frequency of pulsed beam current all can be adjusted conveniently. Highlights: A novel control grid bias power supply is designed for high-frequency pulsed EBW. Chopper technique is used to produce pulsed voltage in the bias power supply. The driving signal of switch tube is transmitted by carrier wave technique. The designed bias power supply can realize 0–20 kHz pulsed EBW.